Annotated checklist of earthworm species described by András Zicsi (Clitellata: Megadrili) - Csuzdi, Csaba; Szederjesi, Tímea; Sherlock, Emma (Zootaxa, 2018)
Professor András Zicsi, the renowed taxonomist and ecologist of earthworms, passed away on 22 July, 2015. He had a decisive impact on earthworm taxonomy in the second half of the 20th century, describing 10 new genus group taxa and 243 species / subspecies new to science distributed in 10 families. A complete list of the new taxa described by Prof. Zicsi is presented here together with references to the original descriptions and the valid names.